Differences in Erythrocyte Indices in the First and Third Months of Hemodialysis in Chronic Kidney Failure Patients at Praya Regional Hospital - Zahira, Jauhara Rana; Agrijanti, Agrijanti; Getas, I Wayan; Zaetun, Siti (Poltekkes Kemenkes Mataram, 2025)
Hemodialysis therapy plays a role in replacing the kidneys' performance in filtering toxins and forming the hormone erythropoietin which forms and matures red blood cells. For this reason, it is necessary to conduct an examination of the erythrocyte index which functions to monitor the severity of anemia caused by chronic kidney failure. This study is a descriptive study with a cross-sectional approach. The sampling technique with purposive sampling is a technique with sample determination according to the researcher with a sample of patients with erythrocyte index examination data in the first and third months of undergoing hemodialysis. Data were analyzed using the Wilcoxon difference test. The total number of complete data of erythrocyte index examination in the first and third months was 22 patients. The average value of the first month erythrocyte index MCV 83.58 fL, MCH 28.31 pg, and MCHC 33.06 g/dL. In the third month the average value of the erythrocyte index MCV 85.35 fL, MCH 28.89 pg, and MCHC 33.90 g/dL. The results of the study stated a significance value of p 0.000 for MCV, MCH value p 0.015, and MCHC value p 0.005. There is a difference in the erythrocyte index in the first and third months of chronic kidney failure patients undergoing hemodialysis